2013
DOI: 10.3846/13923730.2013.799088
|View full text |Cite
|
Sign up to set email alerts
|

Study on Compressive Bearing Capacity of Concrete-Filled Square Steel Tube Column Reinforced by Circular Steel Tube Inside

Abstract: This paper concentrates on the compressive bearing capacity of one composite column of a Concrete-Filled Square Steel Tube (CFSST) reinforced by a circular steel tube inside. Some tests were conducted to consider the compression behaviour of the stub columns under axial compressive loading. Through an elastoplastic limit analysis based on Unified Strength Theory (UST), the ultimate load capacity of the CFSST columns reinforced by inner circular steel tube under axial compression has been derived, which has a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…e ultimate shear capacity of the joint was computed by the principle of limit equilibrium superposition. Based on the aforementioned shear capacity equations of the joint components, the shear load capacity V uC is obtained by equations (4)- (7) to assess the cracked vertical stiffener joint with shear failure in the panel zone. M uC is the computed bending resistance obtained from equation (10).…”
Section: Results and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…e ultimate shear capacity of the joint was computed by the principle of limit equilibrium superposition. Based on the aforementioned shear capacity equations of the joint components, the shear load capacity V uC is obtained by equations (4)- (7) to assess the cracked vertical stiffener joint with shear failure in the panel zone. M uC is the computed bending resistance obtained from equation (10).…”
Section: Results and Validationmentioning
confidence: 99%
“…Since the confining effect of the concretefilled square steel tube is complex, the square tube is firstly equivalent to the circular steel tube using the method of the equal area [7]. Under the axial compressive force on the column, the circumferential tensile stress will decrease the shear capacity of the steel tube, so the circumferential stress σ sθ of the steel tube is considered in the stress state, as shown in Figure 4, where σ sz stands for the compressive stress under axial compression and τ s is the shear stress of the steel tube.…”
Section: Steel Tubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the STCC columns provide greater strength and ductility as well as the lower chance of steel tube buckling compared to the CFST columns (Yu et al 2010). STCC columns were first investigated by Tomii et al (1985Tomii et al ( , 1987, and since then, several research results on the STCC columns have been reported by different researchers in the literature (Han et al 2005(Han et al , 2009Zhang et al 2013;Xiao 2005;Dong, Ho 2015;Lee et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Figure 2(b), the steel tube is constrained by inside concrete so it can bear some vertical load under the ultimate state of the whole column, η is assumed as the strength reduction factor of the steel tube, and then the stress state of steel tubes can be explicated by α)), substitute them into the stress expression of TSUST, the following expression can be obtained: Advances in Civil Engineering 5 en η was obtained as 0.65 by experimentation and statistical data [29], so the ultimate capacity of the steel tube can be calculated by…”
Section: Twin-shear Unified Strength Eory (Tsust)mentioning
confidence: 99%